The Impact of Synthetic Drug Usage on the Mental Health and Education of School Children: A Comprehensive Study - Sinesh, M.; Premalatha, R. (Journal of Neonatal Surgery, 2025)
The prevalence of synthetic drug usage among school children has become a growing concern globally due to its detrimental effects on mental health and academic performance. This comprehensive study investigates the multifaceted impacts of synthetic drug usage on the mental well-being and educational outcomes of school children. The study employs a mixed-methods approach, incorporating quantitative surveys and qualitative interviews with students, teachers, and parents from diverse socio-economic backgrounds. Quantitative data analysis reveals alarming statistics regarding the prevalence of synthetic drug usage among school children, highlighting the need for urgent intervention. Findings indicate a significant correlation between synthetic drug usage and various mental health issues, including anxiety, depression, and psychotic symptoms. Moreover, students who engage in synthetic drug use exhibit higher rates of absenteeism, poor concentration, and diminished academic performance compared to their non-using peers. Qualitative insights shed light on the underlying reasons for synthetic drug experimentation among school children, ranging from peer pressure and curiosity to escapism from stressors such as academic pressure and familial issues. Furthermore, the study identifies a lack of awareness and misconceptions regarding the perceived safety and consequences of synthetic drug use among students. The impact of synthetic drug usage extends beyond individual students to disrupt classroom dynamics and strain teacher-student relationships. Educators report challenges in identifying and addressing substance abuse issues effectively within the school environment, emphasizing the importance of comprehensive prevention and intervention strategies. Parental involvement emerges as a crucial factor in mitigating the risks associated with synthetic drug usage among school children. However, stigma and fear of judgment often hinder open communication between parents and their children about substance abuse. This study underscores the urgent need for collaborative efforts among educators, parents, healthcare professionals, and policymakers to combat the detrimental impact of synthetic drug usage on the mental health and education of school children. Comprehensive prevention programs, targeted interventions, and improved access to mental health resources are essential to safeguarding the well-being and academic success of future generations